Development Cooperation as a Knowledge Creation Process: Rhythmanalytical Approach to a Capacity-Building Project in Zanzibar - Ojala Minna-Liina; Hooli Lauri (Palgrave Macmillan Ltd., 2022)
In development cooperation, the ideas of material support and instructive teaching have increasingly given way to those of reciprocal collaboration and non-material support. In this research, we explore the potential of rhythmanalysis as an approach to studying complex knowledge creation processes in an international development cooperation project. The Zan-SDI project aimed to enhance the geospatial infrastructure in Zanzibar through cooperation between Finnish and Zanzibarian experts. Our rhythmanalysis shows that knowledge creation in the everyday practices of development cooperation is extremely vulnerable to various distractions on multiple spatio-temporal scales. Continuous learning and efforts are required to sustain the project ensemble and knowledge creation. Although new partnerships and inter-organisational collaboration are a source of novelty and innovation, much of their potential remains unrealised without intensive long-term engagement, possibilities to quickly reform the project scheme, and a sufficient combination of financial, material and non-material support.